Dataset: Femtosecond fiber Bragg grating fabrication with adaptive optics aberration compensation - Salter, P; Wooley, M; Morris, S; Booth, M; Fells, J (University of Oxford, 2019)
The data relates to the modelling of laser written fiber Bragg gratings. The spectra were simulated using the coupled mode theory presented in T. Erdogan, J. Light. Technol. 15, 1277 (1997).